The Japanese defense heritage as a dark tourism in Banyuwangi Indonesia: A qualitative study - Goenadhi, Felix; Chairy, Chairy; Rahmiati, Filda; Prayoga, Tasya Zahwa (People and Global Business Association, 2025)
Purpose: This article investigates the development of dark tourism as a form of educational engagement, using several potential defense heritage sites as case studies. Design/methodology/approach: This study was conducted in the Banyuwangi area, focusing on defensive structures built during the Japanese occupation, which were utilized to deter attacks by superior forces during World War II. Primary data were collected through field observations, informal interviews, and documentation. This approach allowed key participants to share their narratives and provide in-depth perspectives. Findings: The empirical analysis revealed that integrating history and education can foster the development of a new form of tourism, transforming heritage sites into distinctive tourist destinations. Involving a broader demographic in this process can create a sustainable tourism model, promoting dynamic and engaging educational heritage tourism experiences. Research limitations/implications: This research highlights the significance of integrating educational tourism and provides detailed insights into dark tourism from theoretical and practical perspectives. Additionally, the study offers recommendations for specific regions suitable for developing dark tourism. Originality/value: This study examines stakeholders' positive approaches to developing this emerging form of tourism and outlines relevant strategies and initiatives undertaken by these stakeholders.